The MRF4 activation domain is required to induce muscle-specific gene expression. - Mak, K L (1992)
MRF4 is a member of the basic helix-loop-helix muscle regulatory factor family that also includes MyoD, myogenin, and Myf-5. Overexpression of MRF4 or the other muscle regulatory factors in fibroblasts converts the cells to differentiated muscle fibers and transcriptionally activates expression of endogenous and cotransfected muscle genes. Although these factors induce a similar phenotype, they also exhibit some distinct biological activities. For example, MyoD trans activates alpha-actin and troponin I reporter genes to very high levels, whereas MRF4 efficiently activates only alpha-actin expression. Since these proteins have a common basic helix-loop-helix domain, it is likely that portions of the proteins outside of this region impart some specificity to the activity of each muscle regulatory factor. As an initial step in determining the mechanism by which MRF4 and MyoD activate gene transcription, the transcriptional activation domain of MRF4 has been characterized. Experiments utilizing chimeric proteins containing the yeast GAL4 DNA-binding domain and portions of the MRF4 protein indicate that the MRF4 activation domain is located within amino acids 10 to 30. This amino terminus is both necessary and sufficient to elicit a transcriptional response in transfected cells. The MRF4 activation domain and the related amino-terminal MyoD activation domain are capable of substituting for one another in converting fibroblasts to a myogenic phenotype and in activating expression of an alpha-actin reporter gene, although the MRF4 and MyoD activation domains on these chimeric proteins also dictate the specificity of transcriptional activation. The different primary amino acid sequences of these regions leave open the possibility that different coregulator proteins interact with the muscle regulatory factors to elicit their correct transcriptional activity during skeletal muscle development.